2018
DOI: 10.1108/sgpe-d-18-00003
|View full text |Cite
|
Sign up to set email alerts
|

Similar or different?

Abstract: Purpose-This paper aims to explore the support experiences of 381 PhD students within the humanities and social sciences from three research-intensive universities in Denmark (n = 145) and Finland (n = 236). The study investigates the cross-cultural variation in the researcher community support and supervisory support experiences, factors associated with their support experienced and the perceived support fit. Design/methodology/approach-The study used a mixed methods design, both quantitative analyses and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…This has involved establishing quality assurance and support systems (Andres et al, 2015), funding opportunities (Ministry of Higher Education and Science in Denmark, 2016; Pyhältö et al, 2015) and increased demands for international cooperation (Finnish Ministry of Education and Culture, 2017; Ministry of Higher Education and Science in Denmark, 2016; Toom & Pyhältö, 2020). The countries also share similar concerns regarding doctoral education, including high drop-out intentions rates (Cornér et al, 2017(Cornér et al, , 2018 and the need to build a more robust social support system for Ph.D. students (Hermann et al, 2014 In both Finland and in Denmark, a doctoral dissertation can be completed either in the form of a monograph or as an anthology, meaning a series of articles that includes a summary.…”
Section: Doctoral Education In Finland and Denmarkmentioning
confidence: 99%
See 1 more Smart Citation
“…This has involved establishing quality assurance and support systems (Andres et al, 2015), funding opportunities (Ministry of Higher Education and Science in Denmark, 2016; Pyhältö et al, 2015) and increased demands for international cooperation (Finnish Ministry of Education and Culture, 2017; Ministry of Higher Education and Science in Denmark, 2016; Toom & Pyhältö, 2020). The countries also share similar concerns regarding doctoral education, including high drop-out intentions rates (Cornér et al, 2017(Cornér et al, , 2018 and the need to build a more robust social support system for Ph.D. students (Hermann et al, 2014 In both Finland and in Denmark, a doctoral dissertation can be completed either in the form of a monograph or as an anthology, meaning a series of articles that includes a summary.…”
Section: Doctoral Education In Finland and Denmarkmentioning
confidence: 99%
“…Based on the findings of previous studies attrition rates can range from 33% to 70% (Gardner & Gopaul, 2012;Ivankova & Stick, 2007;Jiranek, 2010). Also, in the Finnish and Danish context of doctoral education, there is evidence of high drop-out intentions rates (Cornér et al, 2017(Cornér et al, , 2018. It has been shown that research community integration and networks (Castelló et al, 2017;Graham & Massyn, 2019;Jairam & Kahl, 2012;Lovitts, 2001) are vital for reducing attrition rates and to enhance degree completion.…”
Section: Interest In Doctoral Studiesmentioning
confidence: 99%
“…Evaluating aspects related to academic life, we found that many graduate students at some point had considered abandoning their studies. Several studies have reported high rates of university withdrawal intentions, for example, 30–70% of doctorate students will may not complete their PhD degree 8 , 29 31 . Experiences of high stress, anxiety and exhaustion, demonstrated a lack of interest in their studies which appears to influence drop-out intentions 8 , 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Students' performance and achievement depend largely on how successfully they integrate into and navigate a programme, both academically and socially (Hawley, 2010). Students cannot fully achieve this purpose without support from their supervisors and the larger research community (Cornér et al., 2018). Various types of support can significantly improve students' satisfaction with a program and influence their progress.…”
Section: Literature Reviewmentioning
confidence: 99%